2014
DOI: 10.1007/s00423-014-1252-0
|View full text |Cite
|
Sign up to set email alerts
|

Liver failure after hepatocellular carcinoma surgery

Abstract: The developed model could be useful for predicting the occurrence of PHLF in HCC patients with underlying liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Among others, reports by Nanashima et al4344 and Motoyama et al36 suggested that elevated preoperative prothrombin time (>70–80% of normal ranges) independently predicted PHLF.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among others, reports by Nanashima et al4344 and Motoyama et al36 suggested that elevated preoperative prothrombin time (>70–80% of normal ranges) independently predicted PHLF.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, other studies by Li et al 34 and Shen et al 35 reported that a preoperative serum bilirubin level of ≥1.19 mg/dL was a significant independent risk factor for PHLF in patients undergoing liver resection. Motoyama et al 36 also reported a significant correlation between preoperative serum bilirubin and PHLF using the ISGLS criteria and developed a model for prediction of PHLF incorporating serum bilirubin, INR and the presence of intra-operative packed red blood cell transfusion. This model provide stronger correlation with PHLF when compared with MELD score and ICG R15 .…”
Section: Discussionmentioning
confidence: 99%
“…Operation resection is still the preferred treatment for early HCC [1]. However, HCC patients after surgery have decreased immune function, damaged liver function, metastasis, and recurrence [2][3][4]. It has been reported that HCC can be treated by transcatheter arterial chemoembolization (TACE) via superselective segmental embolization [5].…”
Section: Introductionmentioning
confidence: 99%
“…The Model for End-stage Liver Disease (MELD) was initially constructed as a predictor of mortality following transjugular intrahepatic portosystemic shunts (TIPS) and has been adopted as a measure of liver dysfunction for transplantation(21, 22). Preoperative MELD score has been identified as a predictor of PHLI, but it is limited in sensitivity and specificity, particularly when applied to patients without cirrhosis(6, 2325). Postoperative parameters, such as the 50–50 criteria which uses prothrombin time <50% and bilirubin >50 µmol/L on postoperative day five as significant predictors of mortality, have also been used to predict PHLI but are not helpful for identifying high-risk patients prior to operation(2, 26).…”
Section: Introductionmentioning
confidence: 99%